Peran Antioksidan dan Agen Antiinflamasi dalam Proses Penyembuhan Luka Bakar - Nining Nurnanengsih; Fendy Dwimartyono; Adliah Purnawaty Harifuddin (JURNAL RISET RUMPUN ILMU KEDOKTERAN, 2025)
Burns are tissue damage or loss that occurs due to direct exposure to heat sources such as fire, hot liquids or fats, hot steam, radiation, electricity, or chemicals. The process of healing burns is a complex and long-lasting process and involves a repair process that depends on the immune system, there are three stages, namely: inflammation, formation of granulation tissue (proliferation), and remodeling (which can result in scarring). Research objectives and methods to determine the role of antioxidants and anti-inflammatory agents in the burn wound healing process by searching both international and national literature using databases such as PubMed, Google Scholar, ScienceDirect and Elsevier. Based on the results of a literature study from several journals, 3 research journals were obtained that discussed several plants that contain substances that can act as antioxidants and anti-inflammatory agents in the process of healing burns. The following are the results of screening of the journals, including betel leaves (Piper betleLinn.), Aloe Vera (Aloe Vera), Binahong Leaves (Anredera Cordifolia Tenn) have phenolic compounds contained in them, namely flavonoids, alkaloids, tannins, essential oils, saponins, monoterpenes, polyphenols, and steroids that have the potential as antioxidants, antibacterials, anti-have very good effects in the advanced phase, proliferation phase and remodeling phase which play an important role in reducing, shortening, changing the size of the wound edge distance and accelerating wound healing. Based on the results of the review of these journals, it proves the role of antioxidants and anti-inflammatory agents in the process of healing burns.